Pembelajaran Agama Islam pada Sekolah Dasar Suka Maju Kota Subulussalam (Strategi Pembentukan Akhlakul Karimah) - Siti Rahmah; Warul Walidin; Masbur Masbur (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
The aims of this study were: (1) to find out the role of the teacher in learning the Islamic religion in SD Suka Maju, Subulussalam City. (2) To find out the learning strategy applied in SD Suka Maju, Subulussalam City (3) To find out the supporting and inhibiting factors in implementing the akhlakul karimah strategy at SD Suka Maju, Subulussalam City. This study used a qualitative descriptive research method with data collection techniques through interviews, observation, and documents. Data analysis techniques use data reduction, data display, and conclusions or verification. The research location is at SD Suka Maju, Subulussalam City. The results of this study are as follows: 1). The role of the teacher in learning Islamic religion, namely: The teacher carries out his duties as an educator, educates, directs, sets an example or is exemplary, gives advice, reprimands, guides, and gives motivation. And the teacher guides the learning process well and effectively to achieve learning goals. 2). The learning strategies used in Islamic religious education at SD Suka Maju Kota Subulussalam are expository, inquiry learning strategies, problem-based learning strategies, and contextual learning strategies. 3). There are several supporting factors in the formation of Akhlakul Karimah at SD Suka Maju, including Student enthusiasm in the learning process of forming Akhlakul Karimah, Religious activities at school become routines that are carried out at school such as reading Surat Yasin every Friday, Rules that support the realization of the essence of the formation of Akhlakul karimah for SD Suka Maju students, qualified and disciplined teachers, a conducive extracurricular school environment that helps in the formation of Akhlakul karimah for students, and the support and active role of parents and guardians While the inhibiting factors in the formation of Akhlakul Karimah in SD Suka Maju include: different backgrounds of students, lack of interest and enthusiasm of students in learning religion, awareness of less disciplined students, and influence of the environment outside the school.